THE IMPACT OF ECONOMIC FREEDOM ON MACROECONOMIC INDICATORS: THE CASE OF THE NEW FRAGILE FIVE (Third Sector Social Economic Review, 2025)
This study examines the relationship between the Economic Freedom Index (EFI) and macroeconomic variables in the New Fragile Five countries, namely Turkey, Argentina, Pakistan, Qatar, and Egypt. Using panel data analysis covering the years 1999–2022, the impact of economic freedom on macroeconomic performance is evaluated. The analyzed variables include foreign direct investments (FDI), economic growth rates (GDP), inflation (INF), exports of goods and services (EGS), and gross fixed capital formation (GFC).The results reveal that higher levels of economic freedom positively influence macroeconomic performance in the short and medium term. It was found that foreign direct investments and economic growth rates increase significantly in economies with greater economic freedom. Inflation levels are also impacted by economic freedom, supporting price stability. Furthermore, strong relationships between economic freedom and both gross fixed capital formation and export ratios were observed.However, the study also found a weak link between economic freedom and long-term sustainable economic relationships, highlighting that short- and medium-term effects are more pronounced. The research emphasizes the capacity of economic freedom to enhance international trade and investment environments. The findings suggest that policies aimed at increasing economic freedom can support short-term economic performance, but structural reforms are essential for long-term benefits.
Keywords: Economic Freedom Index; New Fragile Five; Panel Data Analysis; Macroeconomic Performance; Economic Growth